Implementasi Kebijakan Kodefikasi Dan Nomenklatur Perencanaan Pembangunan Dan Keuangan Daerah Di Dinas Lingkungan Hidup Dan Pertanahan Provinsi Sumatera Selatan - Putri, Riske Maida; Lisdiana, Lisdiana; Hakim, Arif Rahman (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
In preparing the Strategic Plan (Renstra), the South Sumatra Province Environment and Land Agency faced problems such as the PPTK not understanding the latest policies and activities that overlapped with other fields, and there were still many performance indicators, outputs, and activity outcomes that were not in accordance with the latest regulations. This study aims to implement Minister of Home Affairs Decree Number 050–5889 of 2021 concerning the Results of Verification, Validation, and Inventory of Updating Classification, Codefication, and Regional Development and Financial Planning Nomenclature as a Reference for the Codefication Policy and Regional Development Planning Nomenclature at the Environment and Land Agency of South Sumatra Province so that the problems encountered can be resolved. The research method that will be used is qualitative research, which means that data or information is collected through interviews with informants and uses the George C. Edward III model theory, which uses 4 dimensions (communication, resources, disposition, and bureaucratic structure) to obtain success in implementation. The results of the study show that the implementation of the Decree of the Minister of Home Affairs Number 050–5889 of 2021 concerning Verification Results, Validation, and Inventory of Updating Classification, Codefication, and Regional Development and Financial Planning Nomenclature as a reference for codefication policies and regional development planning and financial nomenclature at the Environment and Land Agency of South Sumatra Province is not yet optimal. These problems are found in inadequate incentive indicators and Standard Operational Procedures (SOPs) indicators that are not in accordance with the latest policies, so that some activities still overlap with activities in other fields.